Cryptocurrencies in the Digital Age : A Holistic Examination of Technology and Trends - Alam, Intikhab (My University, 2024)
This thesis explores the complex world of blockchain technology and cryptocurrencies, offering an investigation of their social effects, economic ramifications, and technical underpinnings. In the introduction, the nature and hypothesis of cryptocurrencies are explained, along with their inherent advantages and disadvantages, as well as the current issues that the industry is facing. The main objective of this thesis is to advance a more logical understanding of the complex interactions among blockchain technology, cryptographic ideas, and the larger field of digital currency. A foundational approach is perceived by the mathematical preliminaries part, which clarifies important cryptographic ideas like symmetric and public-key cryptography, cryptographic protocols, cryptanalysis, and how they relate to blockchain technology. In doing so, the thesis establishes the foundation for evaluating the complexities associated with protecting and authenticating transactions in decentralized systems. As I move on, the investigation of blockchain technology includes a review of its design, workings, and uses in various sectors of the economy. The scalability and performance issues that blockchain is facing are assessed in this section, especially considering its expanding applications. The concluding segment explores the wider ramifications of cryptocurrencies on society, summarizing their influence on society and the dynamic regulatory environment. The dynamic world of cryptocurrencies and tokens, as well as their technological foundations, economic factors, adoption trends, legal frameworks, and the crucial problem of energy consumption from mining operations, are addressed. The thesis’s final remarks provide a succinct overview of the major discoveries and their possible implications for advancing blockchain technology and cryptocurrencies in the future. They also synthesize the insights obtained throughout the thesis.
Keywords: Blockchain technology, Cryptography, Cryptocurrency, Encryption, Security.